Microstructural and mechanical properties of hydroxyapatite-zirconia composites - OKTAR, FAİK NÜZHET; ERKMEN, ZİYA ENGİN (WILEY, 2007)
This work focuses on the improvement of the mechanical properties of hydroxyapatite (HA) through the addition of 3 mol% yttria partially stabilized zirconia (PSZ). Enamel-derived HA (EHA) from freshly extracted human teeth and commercial HA (CHA) were chosen as the matrix. The effects of addition up to 10 wt% of PSZ and of sintering temperature (1000 degrees-1300 degrees C) on the density, microhardness, and compression strength were evaluated. For EHA-PSZ composites, the density and mechanical properties were generally enhanced by adding 5 wt% PSZ, especially after sintering at 1200 degrees C, whereas CHA-PSZ composites showed lower strength values at sintering temperatures of 1200 degrees and 1300 degrees C with respect to EHA-PSZ composites. This may be due to the lower stability of CHA-PSZ composites with higher amounts of calcium zirconate formed over 1100 degrees C when compared with EHA-PSZ composites.
Keywords: SINTERING TEMPERATURE; CERAMICS; REINFORCEMENT; DENTIN; ENAMEL